Cohort profile: A population-based record linkage platform to address critical epidemiological evidence gaps in respiratory syncytial virus and other respiratory infections - Sarna, Mohinder (Minda); Taye, Belaynew; Le, Huong; Giannini, Fiona; Glass, Kathryn; Blyth, Christopher; Richmond, Peter; Glauert, Rebecca; Levy, Avram; Moore, Hannah (International Journal of Population Data Science, 2024)
Introduction The Western Australia (WA) Respiratory Infections Linked Data Platform is a population-based cohort established to investigate the epidemiology of RSV and other respiratory infections in children aged 0-10 years, incorporating microbiological testing patterns, hospital admissions, emergency department presentations, and socio-demographic data. Methods The cohort was formed through individual linkages between datasets from the WA Department of Health including the Birth and Death Registry, Midwives Notification System (MNS), Hospital Morbidity Data Collection, Emergency Department Data Collection, WA Notifiable Diseases Database, WA Register of Developmental Anomalies, WA Cerebral Palsy Register, WA Antenatal Vaccination Database, WA Family Connections, and PathWest Respiratory Virus Surveillance Data. Hospitalisations and emergency department presentations were temporally linked to routine respiratory viral surveillance data. Results The cohort consists of 368,830 WA births between 1 January 2010 and 31 December 2020 with accompanying perinatal and demographic data, and with secondary care follow-up to 30 June 2022. Of these births, 24,660 (6.7%) identify as Aboriginal. A total of 4,077 (1.1%) children died from all causes during the study period (2010-2020), and 9.2% (33,818) of children were born preterm (<37 weeks). Conclusion The Respiratory Infections Linked Data Platform enables epidemiological investigations, identifying virus-specific risk groups, risk factors, clinical presentation, viral testing patterns, long-term impacts and accurate measures of viral incidence rates in risk and population sub-groups This will not only aid in the calculation of cost-effectiveness estimates of interventions such as immunisations, but also provide guidance for design and implementation of such programs to priority groups. The Respiratory Infections Linked Data Platform will also enable evaluation of the direct and indirect effects of maternal and infant vaccines and new therapeutics. Analyses using this platform will also generate epidemiological data needed for other respiratory viruses on the vaccine pipeline such as parainfluenza virus and human metapneumovirus.